Expressão de receptores de padrões moleculares de patógenos no útero bovino ao longo da gestação - Ana Patricia de Carvalho da Silva (2011)
PRRs (pattern recognition receptors) are important components of the innate immunity. They recognize specific PAMPs (pathogen associated molecular patterns). Considering the scarcity of studies about expression of PRRs in bovine pregnant uterus and the uterine response to microorganisms that cause abortion in cattle, this study aimed to characterize the expression of TLR1-10, NOD1, NOD2 and MD2 in bovine pregnant uterus throughout gestation, and to investigate the responsiveness of different regions of the pregnant uterus at the third trimester of pregnancy, by assessing the expression of chemokines after stimulation with heat-killed Brucella abortus, Salmonella enterica serotype Dublin (S. Dublin), Listeria monocytogenes and Aspergillus fumigatus. Total RNA was extracted from endometrium, placentome andintercotiledonary region of cows during the first (n=6), second (n=6) and third trimesters of pregnancy (n=6), and it was subjected to real time RT-PCR. Endometrium and intercotiledonary explants were stimulated with heat-killed microorganisms for 12 hours, followed by RNA extraction and real time RT-PCR. In the placentome, there was no significant variation in TLRs transcription throughout the three trimesters of pregnancy. In the endometrium, there was significant variation in TLR4 and TLR5 transcription during the three stages of gestation; i.e. TLR4 transcription was higher during the first and the third trimester, whereas TLR5 transcription was higher during the last two trimesters. In the intercotiledonary region, there was significant variation in transcription of TLR1/6, TLR7, and TLR8, which were more strongly expressed during the first trimester of pregnancy. At the third trimester of gestation, significanttranscription of CXCL6 and CXCL8 was detected mostly in endometrial tissues in response to purified TLR4 and TLR2 ligands. Transcription of these chemokines was induced in the endometrium and intercotiledonary region at the third trimester of pregnancy when stimulated with heat-killed B. abortus or S. Dublin. Therefore, this study demonstrates that some PRRs are expressed in the uterus during pregnancy, which coincides with its ability to respond to stimulation with TLRs ligands as well as heat-killed organisms known to cause abortion in cattle.